HIFDZ: Partnership Application Based on Peer Teaching As A Platform For Qur’an Memorization - Muthmainnah, Fathimah; Nisa’, Luthfi Farihatun; Baghiz, Ghifran Muhammad; Hanafi, Yusuf (Al-Arabi: Jurnal Bahasa Arab dan Pengajarannya = Al-Arabi: Journal of Teaching Arabic as a Foreign Language, 2023)
231,690,932 Muslims in Indonesia believe in protecting the Qur'an by memorizing or repeating it. However, they have difficulties because they are not tied to the institution of memorizing the Qur’an and need solutions to help memorize the Quran. This research aims to describe the development of the HIFDZ application as a peer teaching-based Al-Qur'an memorization platform. Research method The HIFDZ application uses the Waterfall method, which was first introduced by Winston Royce in 1970 and is often used for Software Engineering (SE) development, including (1) Analytic Needs, (2) Design, (3) Development, (4) Testing, (5) Maintenance. The Peer Teaching approach or peer tutoring is adequate regarding interest and achievement. The practicality of the HIFDZ application was tested on 3 Al-Qur'an memorizers, showing that HIFDZ can be used easily by Al-Qur'an memorizers. Interview results from the HIFDZ application trial with three practitioners who had memorized 30 chapters of the Qur’an showed that the application was excellent and suitable for memorizers of the Al-Qur'an. هناك 231,690,932 مسلمًا في إندونيسيا يؤمنون بحماية القرآن عن طريق حفظه أو ترديده. ومع ذلك، فإنهم يواجهون صعوبات لأنهم غير مرتبطين بمؤسسة تحفيظ القرآن، ويحتاجون إلى حل للمساعدة في حفظ القرآن. الهدف من هذا البحث هو وصف تطور تطبيق HIFDZ باعتباره تطبيقًا قائمًا على التدريس النظير. منصة تحفيظ القرآن الكريم. طريقة البحث يستخدم تطبيق HIFDZ طريقة الشلال التي قدمها وينستون رويس لأول مرة في عام 1970 وغالباً ما تستخدم لتطوير هندسة البرمجيات (SE)، بما في ذلك: (1) الاحتياجات التحليلية، (2) التصميم، (3) التطوير، (4) ) الاختبار، (5) الصيانة. يعتبر أسلوب تدريس الأقران أو تدريس الأقران فعالاً من حيث الاهتمام والإنجاز. تم اختبار التطبيق العملي لتطبيق HIFDZ على 3 من حفظة القرآن الكريم مما يدل على أنه يمكن لحافظي القرآن استخدام HIFDZ بسهولة. أظهرت نتائج المقابلة من تجربة تطبيق HIFDZ مع 3 ممارسين كانوا يحفظون 30 جزءًا من القرآن أن التطبيق كان جيدًا جدًا ومناسبًا للاستخدام من قبل حفظة القرآن.